(untitled) - Hollett, Vicki (Oxford, 2006)
This completely updated edition of Business Objectives contains an interactive CD-ROM. The course develops the skills students need to participate in a variety of business contexts. It offers controlled grammar practice, systematic teaching of relevant vocabulary, and challenging activities that encourage students to use their own business experience.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Textbooks for foreign speakers,Business english,Giáo trình dành cho người nước ngoài,Tiếng Anh thương mại